Strategi Peningkatan Kualitas Lingkungan Kampung-Kota dalam Rangka Pembangunan Kota yang Inklusif dan Berkelanjutan: Pembelajaran dari Kasus Kota Bandung - Iwan Kustiwan; Afrizal Ramadhan (P4W LPPM IPB, 2019)
Among the Sustainable Development Goals (SDGs), there is a goal to create cities and settlements that are safe, resilient, inclusive, and sustainable. In the context of inclusive and sustainable development, all citizens have rights on the city, especially in the context of housing as one of the primary needs that have to be addressed and prioritized by government. All of urban residents, including low-income and urban dwellers, have equal rights to live a decent life, for affordable housing, for healthy residential environment and for equal distribution of public services and basic infrastructure. In this context, the existence of urban kampongs, which dominate urban-housing areas and provide residential area for many low-income communities, needs attention in urban development. The purpose of this study is to formulate generic strategies towards urban kampong quality improvement, both socially and environmentally. Using mix-method (spatial analysis, content analysis, dan SWOT analysis) this paper explains the distribution and characteristics of urban kampongs in Bandung city and formulate strategies to improve the quality of urban kampong environments towards inclusive and sustainable development. This study shows that more than 55% of urban kampong in Bandung belong to the category of slums area. The results of this study concluded that the sustainability status on the socio-economic dimension is still relatively higher compared to physical dimension. This study also formulated strategies both from physical and socio-economic aspects based on case studies in three urban kampong areas in the city of Bandung.